What drives political commitment for nutrition? A review and framework synthesis to inform the United Nations Decade of Action on Nutrition. Issue 1 (10th February 2018) - Baker, Phillip; Hawkes, Corinna; Wingrove, Kate; Demaio, Alessandro Rhyl; Parkhurst, Justin; Thow, Anne Marie; Walls, Helen
Abstract : Introduction: Generating country-level political commitment will be critical to driving forward action throughout the United Nations Decade of Action on Nutrition (2016–2025). In this review of the empirical nutrition policy literature, we ask: what factors generate, sustain and constrain political commitment for nutrition, how and under what circumstances? Our aim is to inform strategic 'commitment-building' actions. Method: We adopted a framework synthesis method and realist review protocol. An initial framework was derived from relevant theory and then populated with empirical evidence to test and modify it. Five steps were undertaken: initial theoretical framework development; search for relevant empirical literature; study selection and quality appraisal; data extraction, analysis and synthesis and framework modification. Results: 75 studies were included. We identified 18 factors that drive commitment, organised into five categories: actors; institutions; political and societal contexts; knowledge, evidence and framing; and, capacities and resources. Irrespective of country-context, effective nutrition actor networks, strong leadership, civil society mobilisation, supportive political administrations, societal change and focusing events, cohesive and resonant framing, and robust data systems and available evidence were commitment drivers. Low-income and middle-income country studies also frequently reported international actors, empowered institutions, vertical coordination and capacities and resources. In upper-middle-income and high-income country studies, private sector interference frequently undermined commitment. Conclusion: Political commitment is not something that simply exists or emerges accidentally; it can be created and strengthened over time through strategic action. Successfully generating commitment will likely require a core set of actions with some context-dependent adaptations. Ultimately, it will necessitate strategic actions by cohesive, resourced and strongly led nutrition actor networks that are responsive to the multifactorial, multilevel and dynamic political systems in which they operate and attempt to influence. Accelerating the formation and effectiveness of such networks over the Nutrition Decade should be a core task for all actors involved.